STUDY ETHNOMATHEMATICS MENGUNGKAP ASPEK-ASPEK MATEMATIKA PADA PENENTUAN HARI BAIK AKTIVITAS SEHARI-HARI MASYARAKAT ADATKAMPUNG KUTA DI CIAMIS JAWA BARAT - Budrisari, Friska (2014)
Study Ethnomathematics: MengungkapAspek-AspekMatematikaPadaPenentuanHariBaikAktivitasSehari-HariMasyarakatAdatKampungKuta di CiamisJawa Barat. Penelitianinibertujuanuntukmenunjukkanhubungantimbalbalikantaramatematikadenganbudaya.Selamainimatematikadianggaptidakmemilikiketerkaitansamasekalidenganbudaya.Fokuspenelitianiniadalahpenentuanharibaikpadaaktivitassehari-harimasyarakatadatKampungKuta, yaitupenentuanharibaikaktivitasbepergian, penentuanharibaikaktivitas di sawah, danpenentuanharibaikaktivitaspembuatangulakawung.Penelitianinimenggunakanpendekatankualitatifdenganmetodeethnography.Teknikpengumpulan data dalampenelitianinimenggunakanprinsip-prinsipdalamethnography, yaituobservasi, wawancara, dokumentasi, danselanjutnyapembuatancatatanlapangan (field notes).Penelitianinidilakukan di KampungKuta yang terletak di DesaKarangpaninggal, KecamatanTambaksari, KabupatenCiamis, ProvinsiJawa Barat.Hasilpenelitianmenunjukkanbahwaadanyaketerkaitanantaramatematikadanbudaya.Penentuanharibaikaktivitassehari-harimasyarakatadatKampungKutadapatdipandangsebagaisesuatu yang berhubungandenganmatematika.Hubungantersebutdapatdilihatdarikonsep-konsepdasar yang terdapatpadapenentuanharibaik, sepertikonseparitmetika (membilang, menjumlahkan, mengurangi, membagi, menghitunghasilbagidansisapembagian). Kata kunci:Ethnomathematics, PenentuanHariBaikAktivitasSehari-Hari, MasyarakatAdatKampungKuta, PendidikanMatematika Study Ethnomathematics: Revealing Aspects of Mathematics onDetermination of Good Day Daily Activities Indigenous KutaVillage in Ciamis West Java. This research aims to show the interrelationship between mathematics and culture. All along mathematics considered to have no relation at all with the culture. The focus of this research is the determination of good day on daily activities of indigenous people of Kutavillage, which is the determination of good day on travelingactivity, the determination of good day on activity in the fields, and the determination of good day on activityin making of kawung sugar. This research used a qualitative approach with ethnography methods. The data collection techniques in this study is using the principles of the ethnography, those are observation, interviews, documentation, and making of field notes. This research was conducted in theKuta villagewhich is located in the Karangpaninggalvillage, District Tambaksari, Kudat District, West Java Province. The results showed that there the interrelationship between mathematics and culture. The determination of good day on daily activities Indigenous people of Kutavillage can be seen as something related to mathematics. These relationships can be seen from the basic concepts contained in the determination of both, such as the concept of arithmetic (counting, adding, subtracting, dividing, calculating the quotient, and remainder of the division) Kata kunci:Ethnomathematics, Revealing Aspects of Mamthematics on Determination of Good Day Daily, Indigenous Kuta Village, Mathematics Education